(untitled) (Research, Society and Development, 2021)
Objective: to identify, through the literature, the costs related to the CME and propose ways to optimize such expenses within the scope of health institutions today. Method: Study of integrative review, through research of scientific literature in the electronic databases Scielo, Lilacs, BVS-ENF and CINAHL. Results: In the time frame from 2007 to 2019, eleven articles were selected that met the search criteria. Costs related to CME are associated with several factors, among them: extensive workload of specialized labor, types of processing and packaging, reprocessing of unused sterile materials and the form of supply adopted by the institution (outsourced processing or products disposable health products). Conclusion: The costs inherent to the CME must be analyzed individually, respecting the routine and specificity of each sterilization center, so that resources and services can be optimized without sacrificing the security of processing.